Realization and fabrication of 3rd order high pass filter with CMOS - Naicker, Koleen; M.Srivastava, Viranjay (International Journal of Engineering and Technology, 2019)
This research work encapsulates the early stages and recent stages of the third order high pass filter design process. The main objective of this work is to design and analysis of the parameters of third order high pass filter using MOSFET technology. It has been designed by cascading a first order with a second order high pass filter. The filter has cut-off frequency of 1 GHz. The core building blocks of the third order high pass filter are the op-amps which are responsible for providing gain in the filter circuit. Therefore, one of the typical LM741 op-amps in the filter circuit has been replaced with two-stage CMOS op-amp for enhanced CMRR, unity gain bandwidth, and reduced power consumption. This will allow the filter to operate for RF transceiver systems. The designed third order high pass filter has implemented double sided design and displayed transient responses have been compared to the simulated results and achieved better filtering effect. The bandwidth of the designed filter is higher than the conventional 3rd order high-pass filter which is also simulated in this work.Â Â